2021
DOI: 10.1021/acs.biochem.1c00081
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Extensions Appear to Frustrate HU Heterodimer Formation by Strengthening Intersubunit Contacts and Blocking the Formation of a Heterotetrameric Intermediate

Abstract: HU is a bacterial nucleoid-associated protein. Two homologues, known as HU-A, and HU-B, are found in Escherichia coli within which the early, late, and stationary phases of growth are dominated by HU-AA, HU-BB, and HU-AB dimers, respectively. Here, using genetic manipulation, mass spectrometry, spectroscopy, chromatography, and electrophoretic examination of glutaraldehyde-mediated cross-linking of subunits, in combination with experiments involving mixing, co-expression, unfolding, and refolding of HU chains,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Higher temperatures result in higher turbidity (Fig. 2 c ), either due to higher molecular kinetic energies (and the consequent increase in protein-protein collisional frequencies), or through enhancement of hydrophobic contributions to intra-molecular and inter-molecular protein interactions, since hydrophobic interactions would be anticipated to be supported by higher temperatures [especially a specific set of hydrophobic stacking interactions between beta sheets of monomers, in HU-B dimers, or between HU-B and nitrogenous bases of DNA, 45 exposed through binding of HU-B].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher temperatures result in higher turbidity (Fig. 2 c ), either due to higher molecular kinetic energies (and the consequent increase in protein-protein collisional frequencies), or through enhancement of hydrophobic contributions to intra-molecular and inter-molecular protein interactions, since hydrophobic interactions would be anticipated to be supported by higher temperatures [especially a specific set of hydrophobic stacking interactions between beta sheets of monomers, in HU-B dimers, or between HU-B and nitrogenous bases of DNA, 45 exposed through binding of HU-B].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that hydrophobic interactions are relevant to HU only in respect of interactions between stacked -sheets at the dimeric interface, which are resistant to disruption by a hydrophobic co-solvent more hydrophobic than HEX, namely dioxane. 45 Effects of electrostatic interactions. There is a rise in turbidity with lowering of pH (Fig.…”
Section: Effect Of Varyingmentioning
confidence: 99%